Assessment and pain management during the triage phase of children with extremity trauma. A retrospective analysis in a Pediatric Emergency Room after the introduction of the PIPER recommendations. - Granata, Carlotta; Guasconi, Massimo; Ruggeri, Francesca; Bolzoni, Marina; Grossi, Cinzia Franca; Biasucci, Giacomo; Cella, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Pain is one of the most common symptoms in children who access the Pediatric Emergency Room (PER). However, many studies show that it is poorly evaluated and treated during the triage phase and that in many cases algometric scales aren’t used for its evaluation. Faced with this, the Piacenza PER (Italy) implemented the Pain in Pediatric Emergency Room (PIPER) recommendations for the assessment and management of pain from the 1st July 2017. The aim of this study was to detect the possible differences in the trend of the outcomes for the detection and treatment of pain in July-October 2016, 2017, 2018. Methods: A retrospective observational study was chosen. 811 discharge letters of extremity traumatized children aged 0-9 years were analyzed, of which 309 referred to the 2016 quarter, 243 to the 2017 quarter and 259 to the 2018 quarter. Results: In 2016, the pain of 12 patients was assessed out of a total of 309, in 2017 of 227 out of 243 and in 2018 of 245 out of 259. The Chi Square test about assessed and not assessed pain, gave statistically significant value (p = 1.36E-98), comparing 2016vs2017 and gave not significant value comparing 2017vs2018 (p = 0.58). 4 patients were treated during the triage phase in 2016, 68 in 2017 and 70 in 2018. Conclusions: Recommendations introduction has increased the frequency of pain algometric measurements during the triage phase by leading to an improvement in the nursing care outcomes in terms of pediatric pain management.